Indocyanine green fluorescence/thermography evaluation of intercostal muscle flap vascularization. Issue 12 (28th September 2018) - Kawamoto, Nobutaka; Anayama, Takashi; Okada, Hironobu; Hirohashi, Kentaro; Miyazaki, Ryohei; Yamamoto, Marino; Kume, Motohiko; Orihashi, Kazumasa
Abstract : Background: During anatomical lung resection in high‐risk patients, the bronchial stump is covered with tissue flaps (e.g. pericardial fat tissue and intercostal muscle) to prevent bronchopleural fistula development. This is vital for reliable reinforcement of the bronchial stump. We evaluated the blood supply of the flap using indocyanine green fluorescence (ICG‐FL) and thermography intraoperatively in 27 patients at high risk for developing a bronchopleural fistula. Methods: Before reinforcing the stump with a flap, the fluorescence agent was intravenously injected and the blood supply was evaluated. The surface temperature of the flap was measured with thermography. The two modalities were then compared. Results: ICG‐FL intensity and surface temperature on the distal compared to the proximal side of the flap decreased by 32.6 ± 29.4% ( P < 0.0001) and 3.5 ± 2.0°C ( P < 0.0001), respectively. In patients with a higher ICG‐FL intensity value at the tip than the median, the surface temperature at the tip decreased by 2.7 ± 1.7°C compared to the proximal side. In patients with a lower ICG‐FL value at the tip, the surface temperature decreased by 4.6 ± 1.7°C ( P = 0.0574). The bronchial stump reinforced the part of the flap with adequate blood supply; none of the patients developed a bronchopleural fistula. Conclusions: ICG‐FL confirmed variation in the blood supply of the intercostal muscle flap, even if prepared using the same surgical procedure. Thermography analysis tends to correlate with the fluorescence method, but may be influenced by the state of flap preservation during surgery.